Rehumanizing Counseling: A Philosophical Inquiry into the Meaning of Presence in the Age of Intelligent Technology - Bila, Hanifa Salsa; Prasetya, Akhmad Fajar (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The advancement of intelligent technology has reconfigured counseling practices, particularly within digitally mediated counseling settings. While technology expands access to mental health services, it also poses risks to the authenticity of counselor presence and the depth of the therapeutic relationship. This study aims to examine the meaning of counselor presence in digital counseling through a phenomenological perspective, as well as to identify key challenges and rehumanization strategies in the era of intelligent technology. A qualitative approach with a philosophical narrative literature review design was employed, drawing on international journal articles and academic books published over the last five years. Data were analyzed using reflective thematic analysis to interpret concepts of presence, intersubjective relations, and the impact of technology on therapeutic experience. The findings indicate that counselor presence in digital counseling shifts from physical co-presence to an intentional and intersubjective phenomenon constructed through mindful attention, reflective awareness, and deliberate emotional engagement. Technology creates a paradox by simultaneously enhancing service accessibility and constraining authentic presence through reduced nonverbal cues, increased cognitive-emotional load, and heightened risks of technology fatigue and burnout among counselors. This review underscores the necessity of rehumanizing digital counseling through mindfulness practices, active adaptation to digital media, and the development of human-centered digital counseling models to preserve meaningful, ethical, and humanistic therapeutic experiences.